MYSTICISM CONCEPT IN THE UNHOLY FILM - Lihawa, Ayu Lestari; Wibowo, Ary Iswanto (Universitas Suryakancana, 2024)
Mysticism is still an unknown field in terms of scientific research so to find out and explore the mysticism in the belief of religions expands to terms of evidence-based research. The concept of mysticism was analyzed in qualitative descriptive research with the emphasis on collective data extracted through numerous findings and evidence shown in the film to the connection between the statement of the concept as whole terms. Mysticism concept can be found in various religious beliefs of small communities with a sense of communicating through God, it gives a sense of enlightenment and connection towards the creator. Mysticism is a part of the different fields that have interested numerous experts in finding such claims that are based on history itself. In scientific fields, mysticism presents a form of union between the creator that experiences extrovertive (oneness) and introvertive (emptiness). The purpose of this research is to find basic understanding of the mysticism concept in broad view. When various activities in black magic and witchcraft may result in miracle phenomena research should be focused on the different cultures and religions far and wide, small or big communities. The main focus of the religion is Christianity and church authorities and the view to be explored in terms of their faith. The findings based on the main characterization are; Loyalty, Curiosity, Responsibility, and Religious Belief. Mysticism emphasizes all sorts of experiences beyond psychological and neurophysics as a whole. The main idea of this research is (1) to find the evidence based on the findings, (2) to determine the related characterization of Alice Pagett, (3) to find the relevance of the concept. The method used aside from qualitative is using theory of numerous experts related to the field of study from e-journals, e-books, and previous research results of interview depth-in and related characterization of the character. There are five pieces of evidence of concept in the film, three evidence of miracle phenomena, and four characterizations of Alice Pagett.